Analysis of the Influence of Entrepreneur’s Psychological Capital on Employee’s Innovation Behavior Under Leader-Member Exchange Relationship - Li, Tingyi; Liang, Wei; Yu, Zhijian; Dang, Xin (Frontiers in Psychology, 2020)
How to make use of the leaders’ psychological capital to improve the innovation behavior of employees is an important issue for the talent management of enterprises today, and it is also the goal that enterprises must pursue if they want to stand out in the fierce competition. Therefore, in this study, 154 enterprises in high-tech area were selected for questionnaire survey. The correlation between lead-member exchange (LMX) relationship (emotion, loyalty, contribution, professional respect), leaders' psychological capital (confidence, hope, optimism, tenacity), and employees' innovation behaviors were analyzed by multivariate regression. Hierarchical regression method was used to examine the mediating effect of the LEX. It was found that confidence, toughness, and contribution were significantly positively correlated with employee innovation behavior (P<0.000). The positive correlation between hope, optimism, emotion, and loyalty with employees' innovation behavior was significant (P<0.05). Emotion, loyalty, and contribution had mediating effects on the leaders’ psychological capital and the innovation behavior of employees. In conclusion, the leaders’ psychological capital can have a significant positive effect on the innovation behavior of employees directly, and it can also have an indirect positive effect on the innovation behavior of employees by maintaining high quality LMX.